Transferring Management Theory to Practice - Duncan, W. Jack (Academy of Management Journal, 1974)
The perceptions of researchers and managers are examined with regard to various aspects of the knowledge utilization process, adding an empirical dimension to earlier descriptive efforts. Substantial disagreement was found to exist between the two groups on many important elements of the knowledge utilization process.